«Project activities Marine cadets of higher educational institutions in the study of physics and its importance for mastering productive ways of knowing - Cherniavskyi, V. (Problems of Engineer-Pedagogical Education, 2018)
The article presents a general theory of design activity of cadets of maritime higher education, which is extremely important for mastering productive ways of knowing. Proved that significant opportunities for the organization of project activity provides content subject "Physics". Determined results provided by the project activity for future specialists river and sea transport and methodical principles of its organization. Thesis there is determined methodological features of project activities and identifies their contents. It is shown that the project activity allows you to build an educational process, not only in the logic of discipline, but in the logic of cognitive activities for each cadet will have personal meaning. It is proved that the content of physics should not be overloaded educational projects, and the best option is the completion of the project as a study section or a particular topic, the knowledge of which will continue to be widely used in professional activities. It is noted that the content of the training project must also be normalized as the need for processing of new information in the short term will reduce the level of assimilation that inevitably would continue rapid forgetting the loss of this information and its relevance for students. It is also proved that inappropriate content complicate the project and, therefore, the information circulated included, must be adapted to the educational level of students and their intellectual capabilities. Determined that the main goal of the project as a model of the educational process is to improve educational results obtained in the study of physics, due to their use in real situations that may arise in future careers. Emphasized that the project activity is not scientific research, but only a preparatory stage to its implementation, so it should be adequate regarding their tasks and requires a comprehensive approach to its organization and methodological support to ensure a balanced establishing the foundations of knowledge.